Odpowiedź:
Zad 1)
[tex]a) 2*x+9=17[/tex]
[tex]2x=17-9[/tex]
[tex]2x=8/:2[/tex]
[tex]x=4[/tex]
[tex]b) 1+3*z-6=13[/tex]
[tex]3z=13+6-1[/tex]
[tex]3z=18 /:3[/tex]
[tex]z = 6[/tex]
Zad 2)
[tex]5*x-7-x=9-2*x-4[/tex]
[tex]5x -x +2x = 9+7-4[/tex]
[tex]6x=12 /:6[/tex]
[tex]x=2[/tex]
[tex]Spr= 5*2-2+4=9+7-4[/tex]
[tex]12=12[/tex]
Zad 3)
[tex]a) 11*x-6=7*x-4[/tex]
[tex]11x-7x=6-4[/tex]
[tex]4x= 2 /:4[/tex]
[tex]x=\frac{2}{4}=\frac{1}{2}[/tex]
[tex]b) 4x-9x=-12-3[/tex]
[tex]-5x=-15/:(-5)[/tex]
[tex]x=3[/tex]
Liczę na naj